"Keep a sinking boat afloat": Class contradictions in a nascent shrimp farmers' cooperative in South China. (15th August 2022) - Huang, Yu
Abstract: Whether producer cooperatives could serve as a stepping stone leading to socialism is a much debated issue in Marxian scholarship. It has now been recognized that producer cooperatives might possess paradoxical potentials of promoting egalitarian economy and democratic management whilst at the same time constructing class hierarchies. So far, agrarian scholars have already identified how pre‐existing social differentiation facilitated privileged members to exploit the marginal non‐members. However, they have not explored how members exercise their agency in challenging the class division. In summer 2013, at the height of China's cooperatization movement, I embarked on a project of "engaged anthropology" to mobilize shrimp farmers in South China to establish a cooperative so as to challenge agribusinesses that squeeze farmers' returns, but members ended up hiring outside labour. However, members tried hard to bridge the hierarchy between investors and workers as well as between managers and labourers in order to expand its membership and build the village's reputation. This paper traces how cooperative members deal with the dilemmas between profit maximization and egalitarian distribution, highlighting the importance of class analysis for a pro‐poor cooperative movement.